IMPLEMENTASI MODEL PROBLEM BASED LERNING (PBL) BERBASIS MEDIA VIDEO INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Fahrun Nada, Ladaina; Khairani, Fadhilah; Pambudhi, Tegar; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of fifth-grade elementary school students in IPAS learning, particularly in science material, became the background of this study. The study aimed to analyze the effect of implementing Problem Based Learning model based on interactive video on student learning outcomes. This study used a quantitative approach with a quasi-experimental research method and the design used was nonequivalent control group. The sample was taken using purposive sampling of 50 students. Data collection was conducted through tests and non-tests. Hypothesis testing using simple linear regression analysis showed a significance value of 0.000 < 0.05 and F_count > F_table (44.005 > 4.28). The research results showed that the implementation of Problem Based Learning model based on interactive video had a significant effect on the learning outcomes of fifth-grade students at SD Negeri 2 Kota Gajah.